DETERMINAN PERDAGANGAN LUAR NEGERI CHINA DENGAN AMERIKA SERIKAT - Rizki, Maysindi Badyu; Aimon, Hasdi (ECOsains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2021)
This study explain the long-term determinants of foreign trade between China and the United State. The Data used are secondary data sourced from World Bank, US Bureau of Labor Statistics, US Bureau of Economic Analysis (BEA), National Bureau of Statistics China, with VECM (Vector Error Correction Mechanism) analysis methode. The study shows different result occur between the variabels of China and United State on foreign trade. United State output has a significant negative effect but China’s output has no significant effect on foreign trade between China and the United State. The price level of the United State and China has a significant effect, but has a different direction. The exchange rate of the United State has a significant positive effect on foreign trade between China and the United State and China’s exchange rate not significant and has a negative effect.